2016
DOI: 10.7314/apjcp.2016.17.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Species are Possible Risk Factors of Cholangiocarcinoma

Abstract: Recently, infection with Helicobacter spp. plays a role in the development of various cancer have been reported including biliary tract carcinoma mainly cholangiocarcinoma (CCA). There has been a strong, positive correlation between opisthorchiasis-associated CCA and infection with Helicobacter. Infection with H. bilis and H. hepaticus species can cause biliary cancer (Chang and Parsonnet, 2010). Recently, Deenonpoe et al (2015) reported liver fluke O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 69 publications
2
13
0
Order By: Relevance
“…However, we found significant associations between smoking and both types of cholangiocarcinoma. As reported in previous studies [ 51 ], duodenal/gastric ulcers, which are thought to be a proxy for Helicobacter pylori infection, were associated with increased risks of both ICC and ECC. However, this finding should be interpreted cautiously because cholangiocarcinoma patients, ECC patients in particular, often undergo endoscopy for diagnosis [ 52 ].…”
Section: Discussionsupporting
confidence: 56%
“…However, we found significant associations between smoking and both types of cholangiocarcinoma. As reported in previous studies [ 51 ], duodenal/gastric ulcers, which are thought to be a proxy for Helicobacter pylori infection, were associated with increased risks of both ICC and ECC. However, this finding should be interpreted cautiously because cholangiocarcinoma patients, ECC patients in particular, often undergo endoscopy for diagnosis [ 52 ].…”
Section: Discussionsupporting
confidence: 56%
“…Several studies have reported Helicobacter spp. in gut-associated cancer development 42 and we found that Rb3/Rd substantially deteriorated Helicobacter abundance (Table S5 ). Moreover, most of the taxa from table-S5 were positively correlating with the expression profile of pro-inflammatory/tumor markers (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…It has been hypothesized that H pylori may play a role in cholangiocarcinogenesis by increasing the cell kinetics of the biliary epithelium and inducing the formation of stones . A meta‐analysis of ten case‐control studies suggests that other Helicobacter species may be also involved in CCA development (cumulative OR = 8.88, 95% CI 3.67‐21.49); however, since CCA patients (especially those with eCCA) often undergo endoscopy, these findings should be interpreted with caution.…”
Section: Risk Factorsmentioning
confidence: 99%